Place-Making Approach in Transforming Community Gardens into Tourist Attractions in Guwosari, Bantul, Yogyakarta - MUTIARNI, Yosi Septa; BANDIYAH, Uswatun Nurul; RIYANISMA, Besti Ismi; SETIAWAN, Risky (PT Keberlanjutan Strategis Indonesia, 2025)
Urban farming in community gardens has been increasingly recognized as spaces that support various activities, from environmental sustainability, community resilience, to food security. Now, these spaces have gotten more attention due to their potential as tourist destinations, providing chances for cultural, educational, and experiential tourism activities. This study examines the potential of the community garden in Guwosari, especially Iroyudan, Bantul, as a tourist attraction using the role of space in sustainable tourism, place-making, and tourism geography. The possibility of a community garden as a tourist attraction is assessed using a qualitative approach to highlight the role of placemaking and particularly explores the key factors for integrating agritourism within urban tourism frameworks. Findings indicate that Iroyudan Community Garden offers rich experiential tourism opportunities, including educational farm tours, farm-to-table experiences, direct agricultural workshops, and cultural heritage integration. However, challenges such as infrastructure limitations, community readiness, and policy support must be addressed to ensure sustainable development.